Dramatic Reduction in 30-Day Readmissions Through High-Risk Screening and Two-Phase Interdisciplinary Care. Issue 12 (December 2017) - Labrada, Mabel; Mintzer, Michael J.; Karanam, Chandana; Castellanos, Raquel; Cruz, Lorinda; Hoang, Minh; Wieger, Regina; Aguilar, Enrique; Florez, Hermes; Ruiz, Jorge G.
Abstract : Objectives: Thirty-day readmissions are common, serious, and costly. Most important, often they are preventable. The purpose of this quality improvement study was to evaluate an interdisciplinary, two-phase intervention to reduce 30-day readmissions among high-risk medical patients. One or two high-risk patients were selected each weekday by a hospitalist using literature-based, locally tested criteria that included common medical illnesses, active psychiatric illness, and recent or recurrent hospital admissions. Methods: Patients admitted to 1 of 5 medical hospitalist teams were selected to receive the intervention; patients admitted to the 4 remaining teams were used for comparison. The two-phase care coordination intervention consisted of a daily interdisciplinary team meeting for the selected high-risk patients and postdischarge interventions that included outpatient care coordination until the patients' first follow-up appointment. The care plan addressed medical/geriatric assessment, social stability, medication reconciliation, nutritional needs, care coordination including future appointments/testing, and community services. Eighty-five patients in the intervention group were compared with 84 patients from the comparison group using propensity score matching. Patient characteristics were similar at baseline. Results: The intervention group demonstrated a reduction in 30-day readmissions by 52% (11 vs 23, P = 0.019). Length of stay was reduced: 5.5 days compared with 7.2 days ( P = 0.258). Conclusions: This intervention produced a significant reduction in 30-day readmissions for high-risk patients and a trend for shorter lengths of stay compared with similarly matched patients. Future research trials are needed to verify these results. Abstract : This article describes a two-phase interdisciplinary intervention (inpatient plus outpatient until the first postacute clinic visit) used to reduce 30-day readmissions in medical patients at high risk for readmission. Four high-risk criteria were developed based on literature reviews and pilot data; they were applied soon after admission. Compared with patients who did not receive the intervention, there was a dramatic reduction in all-cause 30-day readmissions and a trend toward a reduction in bed-days of care.